Technology-supported Acceptance and Commitment Therapy for chronic health conditions: A systematic review and meta-analysis. (January 2022) - Herbert, Matthew S.; Dochat, Cara; Wooldridge, Jennalee S.; Materna, Karla; Blanco, Brian H.; Tynan, Mara; Lee, Michael W.; Gasperi, Marianna; Camodeca, Angela; Harris, Devon; Afari, Niloofar
Abstract: Chronic health conditions (CHCs) are common and associated with functional limitations. Acceptance and commitment therapy (ACT) shows promise in improving functioning, quality of life, and distress across several CHCs. The purpose of this study was to conduct a systematic review of technology-supported ACT for CHCs and perform a meta-analysis on functioning and ACT process outcomes. Multiple databases were systematically searched for randomized controlled trials. A total of 20 unique studies with 2, 430 randomized participants were included. CHCs addressed in these studies were chronic pain ( k  = 9), obesity/overweight ( k  = 4), cancer ( k  = 3), hearing loss ( k  = 1), HIV ( k  = 1), multiple sclerosis ( k  = 1), and tinnitus ( k  = 1). Internet and telephone were the most used technology platforms. All studies included therapist contact with considerable heterogeneity between studies. Random effects meta-analyses found medium effect sizes showing technology-supported ACT outperformed comparator groups on measures of function at post-treatment (Hedges' g  = −0.49; p  = 0.002) and follow-up (Hedges' g  = −0.52; p  = 0.02), as well as ACT process outcomes at post-treatment (Hedges' g  = 0.48; p  < 0.001) and follow-up (Hedges' g  = 0.44; p  < 0.001). Technology-supported ACT shows promise for improving function and ACT process outcomes across a range of CHCs. Recommendations are provided to optimize technology-supported ACT for CHCs. PROSPERO registration number: CRD42020200230. Highlights: Technology-supported ACT outperformed comparison groups on function and ACT outcomes. Technology modality and therapist contact moderated effects. Recommendations provided to optimize technology-supported ACT.